Menstrual cycle phase does not affect carbohydrate supplementation ergogenic effect after heavy intensity cycling - Fleitas-Paniagua, P. R.; Rasica, L.; Azevedo, R. A.; Alvares, T. S.; Zagatto, A. M.; Murias, J. M. (Scandinavian Journal of Medicine & Science in Sports, 2026)
To investigate whether carbohydrates (CHO) supplementation affects endurance performance, perceived and performance fatigability responses following a constant power output (PO) heavy intensity exercise bout across mid-follicular and mid-luteal menstrual cycle phases. Twelve recreationally trained females completed: (i) a step-ramp-step test to estimate gas exchange threshold (GET) and maximal metabolic steady state (MMSSest); (ii) 4 constant-PO bouts for 90 min at Delta20% between GET and MMSSest randomly repeated twice in the mid-follicular and twice in the mid-luteal menstrual cycle phase, drinking either a CHO (F-CHO and L-CHO) or a placebo (F-PLA and L-PLA) beverage. A subsequent 4 km time trial (TT) was performed after each session. Rating of perceived exertion (RPE), rating of fatigue (RoF), dyspnea, leg pain, changes in isometric maximal voluntary contraction (IMVC), voluntary activation (VA), low-frequency fatigue (Db10:100), and potentiated twitch (Qtwpot) were measured in all sessions. The 4 km TT was better (p = 0.005) after F-CHO (9.9 ± 2.1 min) and L-CHO (9.8 ± 2.0 min) compared to F-PLA (10.4 ± 2.6 min) and L-PLA (10.0 ± 1.9 min) similarly for both phases. F-CHO (-46% ± 12%) and L-CHO (-50% ± 12%) showed greater decline compared to F-PLA (-43% ± 12%) and L-PLA (-43% ± 14%) for Qtwpot (p = 0.044). L-CHO (10 (9-10)) showed greater values compared to L-PLA (9 (8-9)) for dyspnea (p = 0.020). No differences were observed for IMVC, VA, Db10:100, RPE, RoF or leg pain. In recreationally trained females: (i) no differences in endurance performance or performance fatigability are observed between the mid-follicular and mid-luteal menstrual cycle phases if 4 km TT is performed after 90 min at Delta20% between GET and MMSSest; and (ii) CHO supplementation improves endurance performance and affects performance fatigability similarly across these menstrual cycle phases.